The sensory, physical and nutritional quality profiles of purple sweet potato and soy-based snack bars for pregnant women - Yosfi Rahmi; Adelya Desi Kurniawati; Rahma Micho Widyanto; Ayuningtyas Dian Ariestiningsih; Addien Zahratul 'Aisyi Al Farahi; Annisa Nafilata Ruchaina; Evita Virginia Sihombing; Fanny Bella Istira; Izzatun Nafsiyah; Katarina Dian Permatasari; Ririk Dwi Anjani; Stephani Anggita Yuli Maharani Simanjuntak; et al. (SAGE Publishing, 2021)
Background: The deficiency of energy, protein, and other beneficial nutrients during pregnancy causes chronic energy deficiency (CED). This condition increases the chance of having babies with low birth weight (LBW) and various other health problems. To meet these nutritional needs, supplementary feeding is necessary in the form of snack bar, using local food ingredients, such as purple sweet potatoes and soybeans (PSPS). This study determines the differences in a few aspects of PSPS snack bar, such as sensory acceptability, physical quality, and nutritional content in several formulations. Design and Methods: The best three formulations were selected through sensory acceptability by involving 40 panelists and showed the following results P0 (commercial product), P2 (80% purple sweet potato: 20% soybean), and P3 (70% purple sweet potato: 30% soybean). Furthermore, these formulations were triplicated for further physical color test, the hardness and breaking force, as well as the nutritional analysis that includes both macro and micronutrients. Results: The results showed significant differences (p<0.05) in the sensory acceptability, physical quality, nutritional content (except carbohydrate and iron), and antioxidant activity. Conclusions: In conclusion, snack bars with 70% purple sweet potato and 30% soybean gave the best formulation.